A validated combined musculotendon path and muscle-joint kinematics model for the human hand. Issue 7 (19th May 2019) - Ma'touq, Jumana; Hu, Tingli; Haddadin, Sami
Abstract: Neuromusculoskeletal models provide a mathematical tool for understanding and simulating human motor control and neuromechanics. In this work, we propose a combined computational model for the musculotendon paths and muscle-joint kinematics for the human hand, including all extrinsic and intrinsic muscles. This model is implemented based on the anatomical descriptions and a human hand dissection study. The model takes joint angles as input and estimates the musculotendon lengths, length change rates, and excursion moment arms. The proposed model is simulated to generate according moment arms, which are compared with cadaver measurements available from literature in terms of similarity coefficient s . For most muscles compared, high similarity with s ≥ 0.70 for 92% of cases is achieved between the modeled and the measured moment arms. These results suggest the correctness of modeled moment arms and imply the feasibility of modeled musculotendon paths, lengths, and length change rates.